Orthogonality criterion for banishing hydrino states from standard quantum mechanics - de Castro, Antonio S. (Elsevier B.V., 2007)
Orthogonality criterion is used to show in a very simple and general way that anomalous bound-state solutions for the Coulomb potential (hydrino states) do not exist as bona fide solutions of the Schrodinger, Klein-Gordon and Dirac equations. (C) 2007 Elsevier B.V. All rights reserved.